An Analysis of the Microsoft Academic Graph - Herrmannova, Drahomira; Knoth, Petr (D-Lib magazine, 2016)
Analyses the Microsoft Academic Graph (MAG), a heterogeneous graph comprised of over 120 million publication entities and related authors, institutions, venues and fields of study that is also the largest publicly available dataset of citation data. Studies the characteristics of the dataset and provides a correlation analysis with other publicly available research publication datasets. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.